2014
DOI: 10.1007/s10961-014-9340-4
|View full text |Cite|
|
Sign up to set email alerts
|

How does working on university–industry collaborative projects affect science and engineering doctorates’ careers? Evidence from a UK research-based university

Abstract: This paper examines the impact of industrial involvement in doctoral projects on the particular nature of the training and careers of doctorates. We draw on an original survey of job histories of doctorates in physical sciences and engineering from a research-based university in the UK. Using multivariate probit analysis and linearised (robust) and resampling (jackknife) variance estimation techniques, we found that projects with industrial involvement are associated with higher degree of socialisation with in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 60 publications
1
21
0
Order By: Relevance
“…Researcher orientation may also have consequences for their careers. As the research shows, physics and engineering Ph.D. researchers' engagement in industry projects negatively affected their career in academia; however, it increased their chances of a career in industry (Lee and Miozzo 2015).…”
Section: Selection Phase Execution Phasementioning
confidence: 99%
“…Researcher orientation may also have consequences for their careers. As the research shows, physics and engineering Ph.D. researchers' engagement in industry projects negatively affected their career in academia; however, it increased their chances of a career in industry (Lee and Miozzo 2015).…”
Section: Selection Phase Execution Phasementioning
confidence: 99%
“…In relation to the incentives that could stimulate engagement in U-I collaborative projects on the part of academics, research should consider that collaboration with industry does not necessarily foster success in academia. As indicated by Lee and Miozzo (2015), the engagement in industry-involved projects by physicists and engineering Ph.D. researchers is negatively related to their career in academia. It is therefore not only up to the university but the entire science system including policy makers to come up with an incentive scheme specifying how and when academics can be promoted if they engage in the third mission of the university.…”
Section: The Institutions In University-industry Collaborationsmentioning
confidence: 99%
“…A literature review on doctoral students' experience of the interaction with industry (Thune, 2009) revealed that those students who are involved in collaborative arrangements have a markedly different training experience than non-collaborative students. In turn, this leads to differences in the skills and competences they develop (Lee & Miozzo, 2015;Wardenaar et al, 2014), which, in the case of industrial doctorates tend to be broader and more aligned with industrial activities of commercialisation and application of knowledge. According to Roberts (2018, p.1), this encourages a rethinking of the professional identity of these doctoral students, who 'acquire an interdependent suite of skills from a range of contexts and set goals in multiple working environments', thus being more versatile than their traditional counterparts.…”
Section: Competencesmentioning
confidence: 99%
“…The research objectives of doctoral students carrying out industrial projects are targeted at solving firm-specific technical problems or developing firm prototypes or specifications. These are also benefiting from the close interaction with industry through meetings and presentations during their doctoral training (Lee & Miozzo, 2015). Thus, they have the opportunity to get familiar with the industrial environment and working practices, which in turn facilitates their transition to a career in industry (Lee & Miozzo, 2015).…”
Section: Competencesmentioning
confidence: 99%